Evaluation of the sustainability of hemp fiber reinforced wheat gluten plastics - Muneer, Faraz (SLU/Dept. of Biosystems and Technology (from 130101), 2012)
Bio-based plastics and composites are getting attention as an alternative to unsustainable petro-chemical based plastics. Hemp fiber reinforced wheat gluten (WG) composites can be an alternative to petro-chemical based plastics in many applications, because of their interesting tensile properties and environmental friendliness. However, the evaluation of sustainability is important before efforts can be made for their commercial production process. In this study three hemp farmers were interviewed for their opinion about hemp fiber reinforced WG composites and future cropping plans. Consumer analysis was done for people’s willingness to choose and pay for hemp fiber reinforced WG composites (80 respondents). The produced composites were subjected to biodegradability test using the ASTM D5988-03 standard. Life cycle assessment analysis (LCA) was also conducted for hemp fiber reinforced WG composites. Farmers have shown a positive response to hemp fiber reinforced WG composites and showed willingness to increase the production of hemp. In consumer analysis 75.3% people said that they will choose hemp fiber reinforced WG plastics, whereas 4.9% said that they will choose synthetic plastics. Forty six percent said that they will pay 10% more whereas 30.6% people said that they will pay 20% more, and the percentage of people who can pay 30% more was 15.8%. Biodegradability analysis shows that the hemp fiber reinforced WG composites are biodegradable with 37% for WG, 29% for glutenin and 34% for gliadin based composites (conversion of carbon into CO2 after 90 days period). Life cycle assessment analysis showed that the hemp fiber reinforced WG composites consume less energy and emit less greenhouse gases compared to synthetic plastics. Hemp fiber reinforced WG composites are sustainable compared to synthetic plastics and are of interest in the future.